GROUNDWATER QUALITY OF THE HYDROLOGICAL BASIN OF AMYROS RIVER, AGIA AREA THESSALY, GREECE - Skordas, K.; Tziritis, E.; Kelepertsis, A. (Bulletin of the Geological Society of Greece, 2010)
The area of Agia (Thessaly, Central Greece) is a highly cultivated region, whose hydrogeochemical status is influenced both by natural and manmade factors. Chemical analyses of 40 groundwater samples from the examined area, revealed that geology has a significant impact to aquifers chemistry, mainly expressed through the presence of carbonate rocks and evaporitic minerals of the Neogene formations of the area., as well as the ultrabasic rocks of the substrate. The manmade influence is assessed through the elevated values of nitrates (values up to 168,7 mg/L). Furthermore, the analytical results of the groundwaters revealed that NO3-, Fe and Se, in several samples, exceeded the EC and SMCL (USEPA) limits. More specifically, the 20% of NO3- samples exceeded the EC limits as well as the 2,5% of Se in samples. The 2,5% of Fe in samples exceeded both the EC and SMCL (USEPA) limits.